2020
DOI: 10.1016/j.conbuildmat.2020.118421
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and durability properties of concrete based on recycled coarse and fine aggregates produced from demolished concrete

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 32 publications
(47 reference statements)
5
48
0
1
Order By: Relevance
“…These results are related to the fines of the crushed sand, which helped reduce the porosity of the concrete. This result is in agreement with the work of Layachi et al [26]. Figure 9 (the water accessible porosity of concrete).…”
Section: Gas Permeabilitysupporting
confidence: 93%
“…These results are related to the fines of the crushed sand, which helped reduce the porosity of the concrete. This result is in agreement with the work of Layachi et al [26]. Figure 9 (the water accessible porosity of concrete).…”
Section: Gas Permeabilitysupporting
confidence: 93%
“…However, only a few studies encompass improving the ITZ of the FRA concrete (FRAC) rather than the optimization of FRA in the concrete. Pereira et al (2012) and Berredjem et al (2020) infer that as the replacement of FRA increases, workability and strength of the concrete reduces, but upon addition of SP, the strength of the concrete was increased even at 100% replacement. The study reported that weakness of ITZ due to the higher porosity of FRA decreases the strength of FRAC.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of porous-adhered mortar with its high porosity and water absorption capacity may result in reduced workability and fresh-state performance for the same w/c ratio. This can be compensated for by pre-soaking the aggregates and/or adjusting the added water to account for the increase in water absorption of the RAs (Behera et al, 2014;Berredjem et al, 2020;Kapoor et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These techniques have been demonstrated as being effective in mitigating the negative effects on durability of RAC, in terms of reduced resistance to chloride penetration, sulfate attack, carbonation penetration, and freeze-thaw cycles, attributed to the reasons outlined above (Zhu et al, 2016;Guo et al, 2018;Ma et al, 2019;Berredjem et al, 2020). The presence of higher CSH gel in RAC, because of higher binder content in the attached mortar, can also contribute to chloride binding (Guo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%